Dealing With an Innovative Industry: A Look at Flavored Cigarettes Promoted by Mainstream Brands - Lewis, M. Jane (© American Journal of Public Health 2006, 2006)
Product and marketing innovation is key to the tobacco industry’s success. One recent innovation was the development and marketing of flavored cigarettes as line extensions of 3 popular brands (Camel, Salem, and Kool). These products have distinctive blends and marketing as well as innovative packaging and have raised concerns in the public health community that they are targeted at youths. Several policy initiatives have aimed at banning or limiting these types of products on that basis. We describe examples of the products and their marketing and discuss their potential implications (including increased smoking experimentation, consumption, and “someday smoking”), as well as their potential impact on young adults.